MANAJEMEN PEMBENIHAN IKAN MAS (Cyprinus carpio L.) SECARA ALAMI DI INSTALASI PERIKANAN BUDIDAYA (IPB) PUNTEN, KOTA BATU, JAWA TIMUR - Fernando, Amedio Ferdinand; Farid, Akhmad (Universitas Islam Madura, 2024)
The large market demand for consumption fish makes some farming communities interested in farming, especially consumption fish farming. Fish hatchery business is the first step to the success of fish farming, because for each growing season the aquaculture business requires a supply of seeds from the hatchery business. Goldfish hatcheries are relatively easy because carp can spawn naturally or artificially. Goldfish have a relatively high fecundity or number of eggs, which ranges from 84,000-110,000 eggs per kilogram of brood. The implementation of carp hatchery techniques includes several processes, namely pond preparation, brood selection, kakaban installation, brood release, spawning, hatching eggs, larval care, checking water quality, seeding, pest and disease control. calculation of fecundity, fertilization rate (FR), hatching rate (HR), and survival rate (SR). The data collection method used in this street vendor is primary data. Primary data include active participation, observation, interviews, and documentation. The carp hatchery technique (Cyprinus carpio L.) at IPB Punten, Batu City is carried out naturally, the carp mother used comes from Punten using a ratio of male to female parents of 1: 3. The feeding method, namely Blind Feeding, obtained an F value of 40,000 eggs, FR 84%, HR 84.5% and SR 90.2%.